Assessing the effect of income inequality on household energy poverty—empirical evidence from China - Wang, Dong; Fang, Tingwei; Wang, Xiaofan (Frontiers in Energy Research, 2024)
Eliminating energy poverty is not only a prerequisite for escaping the “energy poverty trap” but also crucial to enhancing the welfare of residents and realising ecological civilization. Income inequality has become an essential challenge affecting China’s economic growth and social stability. By integrating Chinese household data for 2016, 2018, and 2020, a mixed-method approach of energy income response modeling, income inequality measurement modeling, and fixed panel modeling is used in this paper to explore the relationship between income inequality and household energy poverty. Further, the mechanism of income inequality on energy poverty and the poverty reduction effect of household income on energy poverty are explored. The results show that income inequality is significantly and positively correlated with household energy poverty, implying that widening income inequality leads to energy “poverty enhancement.” In terms of mechanisms, income inequality increases energy poverty by increasing households’ willingness to save and reducing energy consumption. The moderating effect analysis shows that the breadth of digital financial inclusion reduces the contribution of income inequality to household energy poverty. The increase in household income will increase the affordability of households, especially the increase in wage income and property income, which can help households lift themselves out of “energy poverty.” Therefore, creating sustainable digital ecosystems, incorporating sound government interventions, and providing diversified income channels are key to helping households escape energy poverty.